Geographical and Temporal Diversity of ‘Candidatus Phytoplasma solani' in Wine-Growing Regions in Slovenia and Austria - Mehle, Nataša; Kavčič, Sanda; Mermal, Sara; Vidmar, Sara; Pompe Novak, Maruša; Riedle-Bauer, Monika; Brader, Günter; Kladnik, Aleš; Dermastia, Marina (Frontiers in Plant Science, 2022)
As the causal agent of the grapevine yellows disease Bois noir, ‘Candidatus Phytoplasma solani’ can have major economic impact on grapevines. To improve the control of Bois noir, it is critical to understand the very complex epidemiological cycles that involve the multiple ‘Ca. P. solani’ host plants and insect vectors, of which Hyalesthes obsoletus is the most important. In the present study, multiple genotyping of the tuf, secY, stamp, and vmp1 genes was performed. This involved archived grapevine samples that were collected during an official survey of grapevine yellows throughout the wine-growing regions of Slovenia (from 2003 to 2016), plus samples from Austrian grapevines, stinging nettle, and field bindweed, and insect samples (collected from 2012 to 2019). The data show that the tuf-b2 type of the tuf gene has been present in eastern Slovenia since at least 2003. The hypotheses that the occurrence of the haplotypes varies due to the geographical position of Slovenia on the Italian–Slovenian Karst divide and that the haplotypes are similar between Slovenian and Austrian Styria were confirmed. The data also show haplotype changes for host plants and for H. obsoletus associated with ‘Ca. P. solani’, which might be linked to new epidemiological cycles of this phytoplasma that involve not just new plant sources and new insect vectors, but also climate and land use changes.